Konsep Khilafah Islamiyyah dalam Tafsir Klasik dan Kontemporer - Bambang Supriadi (UIN Sunan Gunung Djati Bandung, 2021)
The study of the Islamic caliphate is always interesting to discuss until now—either from a historical perspective, Islamic politics, or the interpretation of the Qur'an. Al-Qur'an as the holy book of Muslims, is believed to be eternal against all changes in time and place (sahih li kulli zaman wa makan) certainly gives signs about Islamic government (Khilafah Islamiyyah). This is clarified by the reading of the text of the Qur'an by the commentators, so that in this study it is expected to be able to conceptualize or construct the Khilafah Islamiyyah comprehensively in terms of various classical and contemporary commentaries. This study uses qualitative research methods, namely research that contains written data such as documents or other texts that are relevant to the topic of discussion, this written data is usually in the form of words or actions and not in the form of numbers (numeric). The collection of sources in this study was obtained using library research or book surveys. There are three steps in this technique. First, take an inventory of the verses about the Khilafah Islamiyyah. Second, reading, exploring, and collecting the interpretations of classical and contemporary commentators. Third, describe and analyze the concept of the Islamic Caliphate, so that comprehensive and holistic research findings or results can be obtained.